2017
DOI: 10.1002/mar.20992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matching and Mismatching Messages on Purchase Avoidance Behavior following Major Disasters

Abstract: Following major disasters, purchase avoidance behavior toward products that are caused by stigma often results. For example, after the Tohoku Earthquake and Fukushima Daiichi Nuclear Disaster, consumers have avoided products from Fukushima. Attempts have been made to diminish this purchase avoidance behavior, but they have been found to be ineffective. The reasons for ineffectiveness of strategies within this context were empirically examined based on matching and mismatching effects of messages. In two studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…They held explicitly positive attitudes toward products from both regions. These results are consistent with those of previous work ( Miura et al., 2016 ; Kudo and Nagaya, 2017 ) that found that Japanese consumers in general do not currently have negative implicit or explicit attitudes toward products from Fukushima.…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…They held explicitly positive attitudes toward products from both regions. These results are consistent with those of previous work ( Miura et al., 2016 ; Kudo and Nagaya, 2017 ) that found that Japanese consumers in general do not currently have negative implicit or explicit attitudes toward products from Fukushima.…”
Section: Methodssupporting
confidence: 93%
“…These were more predominant in the region near Fukushima (i.e., Tokyo) than in the region further away (i.e., Hiroshima). The results of recent research and market surveys ( Miura et al., 2016 ; Kudo and Nagaya, 2017 ; Ministry of Agriculture, Forestry, and Fisheries, 2018 ) suggest that the current consumption situation embraces the apparent contradiction that products from Fukushima are somehow avoided by consumers who have no negative attitudes toward them. Focusing on the implicit attitudes and where consumers live, we succeeded in demonstrating a stepping stone toward the resolution of this paradox.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In marketing and consumer research, this category of stigma acquires peculiar traits. Consumers might get stigmatized simply because they buy or use a stigmatized product (Kudo & Nagaya, 2017). Also, after product-harm crises, products from the same country of origin of the product that went through the crisis get stigmatized by association, negatively affecting consumers' preferences.…”
Section: Stigma By Associationmentioning
confidence: 99%